القسم في اللغة الانكليزية والعربية (University of Mosul-college of Basic Education, 2009)
يقسم الناس دائما، وحياتنا مليئة بالوعود التي ربما نفشل بالحفاظ عليها حيث ان الوعود مقدسة ويجب الحفاظ عليها، والقسم هو ان تدعو اسم الله لكي نؤكد بان الشخص يقول الحق وان تقول شى ما وبشكل مؤكد لكي تقول الحقيقة او ان تجعل شخصا ما يقسم رسميا او جعله يخفي سرا. ويقسم الناس عادة بالاشياء المهمة والاشياء العزيزة عليهم لتاكيد او انكار شى ما، وفي هذا البحث نتعرف الى عبارات القسم في العربية والانكليزية والهدف هو ان نبحث استخدام القسم في كل من العربية والانكليزية والادوات التي يحقق من خلالها والاشياء المحلوف بها والغرض من القسم هو اضافة تاكيد اكثر الى النص في شهادة مقدسة، والقسم يستخدم في الادب العربي وبشكل واسع في القران الكريم لكي يؤكد قول الحقيقة. كما تطرقنا الى شرح الفروقات الحضارية بين العربية والانكليزية فيما يخص القسم ودور الحضارة في تحديد السلوك الاجتماعي للناس حيث تكون اللغة جزءا مهما من ذلك، وكذلك هنالك ترابط وثيق بين الحضارة والمجتمع لايمكن فصلها. وقد اهتم علماء اللغة العربية بالقسم اكثر من الانكليز نتيجة الاختلافات الحضارية بين اللغتين حيث ان الانكليزية تمتلك وسائل حلف قليلة مع ذلك ففي اللغة الانكليزية تستخدم عبارات تاكيدية لكي يفترضوا ان اقوالهم صحيحة ويستخدم بعض الناس القسم كوسيلة للخداع، مع ذلك يمكن الاستغناء عن القسم لانه يرخص اسم اللهPeople swear constantly ,our life is full of promises which may fail to keep. Promises are sacred and must be kept .Swearing is calling on the name of God to ensure that one is saying the truth, swearing is to say something solemnly or emphatically to tell the truth,or cause somebody to take the oath of the office or make somebody swear to keep the secret. People usually swear by important things and all that hold dear to confirm or deny something . In this work , we present the swearing expressions in English and Arabic.The aim is to investigate the use of swearing in both English and Arabic , the devices through which it is achieved and the objects sworn by.The purpose of swearing is to add more emphasis to the text in a solemn testimony It is used in Arabic literatute and widely used in the Quran to confirm that a person is saying the truth. Swearing devices in Arabic and objects sworn by in Arabic poetry were presented. Cultural differences between Arabic and English were also explained.The role of culture in determining the social behaviour of people of which language is an important part is also discussed.The relationship between culture and society is so strong that they cannot be separated from each other.Arab linguists paid more attention to swearing than English ones due to cultural differences between the two languages.English has few jurative devices to swear,however, in English they use emphatic statements to assume that their saying is true.Some people use swearing as ameans of deception.Yet,one can do with swearing because it cheapens the name of God